Single-cell analysis of CD14+CD16+ monocytes identifies a subpopulation with an enhanced migratory and inflammatory phenotype - Ruiz, Vanessa Y.; Calderon, Tina M.; Leon-Rivera, Rosiris; Chilunda, Vanessa; Zhang, Jinghang; Berman, Joan W. (Frontiers in Immunology, 2025)
Monocytes in the central nervous system (CNS) play a pivotal role in surveillance and homeostasis, and can exacerbate pathogenic processes during injury, infection, or inflammation. CD14+CD16+ monocytes exhibit diverse functions and contribute to neuroinflammatory diseases, including HIV-associated neurocognitive impairment (HIV-NCI). Analysis of human CD14+CD16+ monocytes matured in vitro by single-cell RNA sequencing identified a heterogenous population of nine clusters. Ingenuity pathway analysis of differentially expressed genes in each cluster identified increased migratory and inflammatory pathways for a group of clusters, which we termed Group 1 monocytes. Group 1 monocytes, distinguished by increased ALCAM, CD52, CD63, and SDC2, exhibited gene expression signatures implicated in CNS inflammatory diseases, produced higher levels of CXCL12, IL-1Ra, IL-6, IL-10, TNFα, and ROS, and preferentially transmigrated across a human in vitro blood-brain barrier model. Thus, Group 1 cells within the CD14+CD16+ monocyte subset are likely to be major contributors to neuroinflammatory diseases.